Selected, new proposals of geotouristic attractions from Lower Silesia - Lorenc, Marek W.; Mazurek, Sławomir (Geotourism/Geoturystyka)
The Lower Silesia is the region of the largest diversity of igneous, sedimentary and metamorphic rocks used for construction and decoration. These rocks are extracted in numerous quarries, which are generally inaccessible for tourists. Hence, the educationally important, unique or just interesting sites remain unknown and cannot be included into the educational activity. However, there is a great number of abandoned quarries, which have been densly vegetated since the closure and which were rather distant from popular tourist trails. Among them are many sites of significant historical value due to the age of exploitation or particular stones then used for construction of important historical monuments or for carving the stonework or sculpture masterpieces. The following paper presents the currently operating quarries with the reference to modern buildings in Wrocław, in which specific stones were used. Moreover, the abandoned quarries were described, which may become tourist and geotourist attractions if properly developed and provided with relevant information.